Nutrition, Gut Microbiota, and Epigenetics in the Modulation of Immune Response and Metabolic Health - Bacaloni, Sabrin; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2025)
Immune system function is intricately shaped by nutritional status, dietary patterns, and gut microbiota composition. Micronutrients such as vitamins A, C, D, E, B-complex, zinc, selenium, iron, and magnesium are critical for maintaining physical barriers, supporting immune cell proliferation, and regulating inflammation. Macronutrients—including proteins, fats, and carbohydrates—also modulate immune responses through their impact on immune metabolism and the gut-immune axis. Epigenetic mechanisms, including DNA methylation, histone modifications, and microRNA expression, mediate the long-term effects of diet on immune function and tolerance. Diet-induced alterations in gut microbiota further influence immune homeostasis via microbial metabolites like short-chain fatty acids. Imbalanced diets, particularly the Western diet, contribute to immune dysregulation, chronic inflammation, and the development of metabolic disorders such as obesity and type 2 diabetes. While plant-based and Mediterranean dietary patterns have shown anti-inflammatory and immunoregulatory benefits, gaps remain in understanding the long-term epigenetic impacts of these diets. This review integrates current knowledge on how nutrition and the microbiome regulate immunity, highlighting future directions for personalized dietary strategies in preventing chronic immune-related conditions.